Inquiry about Domestic Violence against Women in Healthcare Uganda: Do Practitioner Attitudes, Role Conflicts, Efficacy, Safety Concerns and Support Networks Play a Role? - Ehrenberg, Louise; Lawoko-Olwe, Winnie; Loum, Bishop; Oketayot, Kenneth; Akot, Margarete; Kiyembe, Charles; Ochola, Emmanuel; Guwatudde, David; Lawoko, Stephen (Psychology, 2014)
We scrutinized the extent of inquiry about domestic violence against women by practitioners in healthcare Uganda, and its relationship with individual, professional and organization factors. Specifically, we hypothesized that the frequency of IPV inquiry in healthcare would be associated with practitioner attitudes, professional role conflicts, self-efficacy, provider/client safety and system support. Methods: The Domestic Violence Healthcare Provider Survey Scale questionnaire was administered to a random sample of 376 health care providers (n = 250 valid responses) from Gulu, Anaka, Lacor and Iganga hospital situated in northern and eastern Uganda. The data was analyzed using chi-square tests, correlation tests and ordinal regressions analyses. Results and Conclusions: We found that over a three-month period, the majority of participants (31%) had inquired about domestic violence exposure among clients between 4 - 6 times, with 18% having not inquired at all. As hypothesized, low self-efficacy, poor availability of a support network, high professional role conflicts/fears of offending patients, and concerns about victim/provider safety reduced the probability of IPV inquiry. These findings have implications for the reorganization of the health care settings, review of organization policy and further training of car
Keywords: Domestic Violence; Screening; Women; Healthcare; Uganda; Predictors